Morphological and flow-cytometric analysis of haemin-induced human neutrophil activation: implications for transfusion-related acute lung injury - Kono, Mari (Edizioni SIMTI – SIMTI Servizi Srl, 2013)
BACKGROUND: Transfusion-related acute lung injury (TRALI) is associated with vascular endothelial cell injury following neutrophil activation. Recently, it has been suggested that haem-related molecules induce activation of neutrophils and that erythrocyte-derived substances contained in blood preparations are involved in TRALI. We observed the morphological effects and reactive oxygen species (ROS) production of haem-related molecules and investigated the effects of signal transduction inhibitors on haem-induced neutrophil activation. MATERIALS AND METHODS: The polymorphonuclear cell fraction was isolated and stimulated using a control stimulant, PMA or fMLP, or by haem-related molecules, haemin, ferric citrate, or protoporphyrin IX. After stimulation, neutrophil was analysed using electron microscopy, a flowcytometer (FCM) and confocal laser scanning microscope to determine the fluorescent intensity of aminophenyl fluorescein (to detect ROS). RESULTS: In FCM analysis, haemin and protoporphyrin IX, both of which have a porphyrin ring, induced ROS production in neutrophils. Ferric citrate, which has no porphyrin ring, did not induce neutrophil activation. Haemin alone induced ROS production at relatively high concentrations, whereas low-level fMLP acted as an agonist in the presence of low concentrations of haemin. Haem-related molecules induced ROS production in neutrophil granules through signal transduction in a way similar to PMA. However, in electron microscopy studies, haemin stimulated neutrophils showed minute process at their surface and did not show the vacuolation observable following stimulation with PMA or fMLP. DISCUSSION: We suggest that low concentrations of haem-related molecules with porphyrin rings in the presence of other stimulating agent are important for ROS production and possibly the onset of TRALI. The ROS production induced by these molecules is dependent on a signal transduction pathway in a way similar to PMA.